2014
DOI: 10.5012/bkcs.2014.35.9.2635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,4,5-Trisubstituted Isoxazoles through Gold-Catalyzed Cascade Cyclization-Oxidative Alkynylation and Cyclization-Fluorination of 2-Alkynone O-Methyloximes

Abstract: Gold-catalyzed tandem cyclization−oxidative alkynylation and cyclization-fluorination reactions of 2-alkynone O-methyloximes are described. The reactions proceed smoothly at room temperature in the presence of 10 mol % of (PPh 3 )AuNTf 2 , 2.5 equivalents of selectfluor, and 2 equivalents of K 3 PO 4 . 2-Alkynone Omethyloximes undergo intramolecular oxyauration/cyclization and ensuing oxidative cross-coupling and fluorination process to afford the corresponding 3,4,5-trisubstituted isoxazoles in a cascade mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In this case, mechanistic studies suggested that only a redox Au­(I)/Au­(III) catalytic cycle could account for the formation of fluoroisoxazoles. Furthermore, the group of Ryu studied the possibility to perform a gold-catalyzed oxidative cross-coupling reaction using phenylacetylene derivatives 874 as coupling partners (Scheme , part C) . After a thorough investigation of the reaction conditions, a series of alkynylisoxazoles 875 could be obtained from alkynyloxime dervatives 873 in moderate yields (30–47%) and under relatively mild conditions.…”
Section: Carbon π-Systems With Electron-withdrawing Groupsmentioning
confidence: 99%
“…In this case, mechanistic studies suggested that only a redox Au­(I)/Au­(III) catalytic cycle could account for the formation of fluoroisoxazoles. Furthermore, the group of Ryu studied the possibility to perform a gold-catalyzed oxidative cross-coupling reaction using phenylacetylene derivatives 874 as coupling partners (Scheme , part C) . After a thorough investigation of the reaction conditions, a series of alkynylisoxazoles 875 could be obtained from alkynyloxime dervatives 873 in moderate yields (30–47%) and under relatively mild conditions.…”
Section: Carbon π-Systems With Electron-withdrawing Groupsmentioning
confidence: 99%
“…Recently, Jurberg and co-workers developed a palladiumcatalyzed cross-coupling strategy for the synthesis of 3,5-disubstituted isoxazoles using 5-( pseudo)halogenated isoxazoles as the platform molecule (Scheme 21). 40 With triflate substituted isoxazoles (42) as the optimal substrate, the well-known Sonogashira and Suzuki cross-coupling can be easily achieved, thus generating the corresponding alkynylation products (44) and arylation (46) products in moderate to good yields.…”
Section: Scheme 16mentioning
confidence: 99%
“…In 2014, Ryu and co-workers developed a gold-catalyzed cascade cyclization-oxidative alkynylation and cyclizationfluorination of alkynyl O-methyl oximes (54) (Scheme 26). 44 Further screening of the reaction conditions revealed that both (PPh 3 )AuNTf 2 and K 3 PO 4 were indispensable for this protocol. The authors also explained that the role of K 3 PO 4 is to abstract the acetylenic proton of the terminal alkyne and produce a gold-acetylide species.…”
Section: Gold Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, cyclization of alkynyl oxime ether has aroused much attention which is summarized in Scheme . Ryu, Larock, and Ruchirawat et al utilized electrophilic cyclization of alkynyl- O -methyl oximes for the synthesis of 4-haloisoxazoles, respectively (Scheme a). Chen and our group developed palladium-catalyzed coupling between alkynyl- O -methyl oximes with activated alkenes/alkynes for the construction of 4-alkeny/alkyny isoxazoles (Scheme b,c).…”
Section: Introductionmentioning
confidence: 99%